Analysis of the Effectiveness and Efficiency of Performance Management on Financial Performance Papua Province - Syaiful Rizal Sjuaib; J. Ary Mollet; Hans Z. Kaiwai (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This study aims to measure the effectiveness and efficiency of regional financial management performance in Papua Province, identify obstacles in the management of regional financial performance, and formulate strategies to improve financial management in order to enhance financial performance of Papua Province. Methodology/approach: This research employs a mixed-methods approach. Data were collected through interviews and documentation. Data analysis techniques include quantitative analysis using financial ratios, qualitative analysis, and SWOT analysis. Results/findings: Papua’s financial performance shows strengths in local revenue collection and debt service. However, challenges persist, including unstable revenue growth, low fiscal independence, and inefficiencies in spending. Conclusions: Despite progress, weaknesses in governance, human resources, and digital systems limit financial sustainability. Systemic reform is needed to strengthen performance. Limitations: The study is limited to the 2019–2023 period and focuses only on provincial-level data, excluding sub-unit analyses. Contribution: This research offers practical recommendations for improving financial governance and supports regional autonomy efforts in challenging contexts.